The The Musical Performance Identity of Ayak Gedhog in the Siswa Laras Tayub Ensemble, Trenggalek Regency, East Java - Martha Ranty Nurvika; Ananto Sabdo Aji; Win Maw Oo (Keteg : Jurnal Pengetahuan, Pemikiran dan Kajian Tentang Bunyi, 2026)
This article, titled “The Musical Performance Identity of Ayak Gedhog in the Siswa Laras Tayub Ensemble, Trenggalek Regency, East Java,” investigates the unique musical and cultural characteristics of this specific repertoire. Utilizing Martin and Nakayama's theory of ethnic and cultural identity, alongside George M.'s identity framework, this study aims to dissect the elements shaping the ensemble's distinct musical treatment. Data were systematically collected through observation, in-depth interviews, and literature studies focusing on the garap (musical treatment) of the Ayak Gedhog by the Siswa Laras ensemble. The findings reveal four key points. First, Ayak Gedhog possesses a specific musical form and an ayak-ayakan structural framework, with a presentation sequence flowing from the bukå (opening), to the main balungan (skeletal melody), and ending with the suwuk (conclusion). Second, the repertoire serves three primary functions: as the opening piece for the tayub performance, as a dance accompaniment for the gedhog tayub, and as a welcoming tribute for distinguished guests. Third, the identity-forming elements of Ayak Gedhog are categorized into stable garap elements (encompassing performance material, performers, facilities, and tools) and situational garap elements (comprising performance determinants and considerations). Finally, the performance identity of the Tulungagungan tayub plays a pivotal role in formulating the garap identity developed by the Siswa Laras ensemble in Trenggalek.